Unemployment Repercussions on the Colombian Productive Structure - Vallejo Zamudio, Luis E. (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Colombia and the world are experiencing a considerable painful labor situation, caused by the COVID-19 pandemic. According to preliminary calculations made by international organizations such as the World Bank and the Economic Commission for Latin America (ECLAC), and national organizations such as the Colombian Department of Statistics (DANE, by its acronym in Spanish), the loss of jobs in relation to the world economy in the first semester of 2020 was 400 million, while for the Colombian economy in the second quarter of the same year it was approximately five million.